Clinical characteristics and management of patients with rosacea in a tertiary dermatology center in Singapore from 2009 to 2013. (26th February 2018) - Cheong, Kah Wai; Yew, Yik Weng; Lai, Yi Chun; Chan, Roy
Abstract: Introduction: Rosacea is a common chronic facial skin disease. A multiethnic society such as Singapore provides an opportunity to evaluate the demographic characteristics and their impact on clinical outcome in rosacea. Aims: The aim of this study was to evaluate characteristics and outcome of rosacea in a multiracial population in Singapore. Methods: Records of all rosacea patients between January 2009 and December 2013 were retrospectively retrieved from the electronic medical records (EMR). Descriptive analysis was performed to understand the characteristics of patients with rosacea. Multivariate logistic regression was used to evaluate the associations between the various variables and types of rosacea as well as the clinical outcome. Results: A total of 1340 patients were identified. The mean age at presentation was 42.8 years with a female predominance (65%). Most of the patients had erythematotelangiectatic rosacea (ETR) (56.3%) followed by papulopustular rosacea (PPR) (37%). With multinomial logistic regression, controlling for age, gender, and known triggers, Indians and Caucasians were more likely to have PPR compared to ETR (OR: 3.4, P = 0.01 and OR: 2.1, P = 0.01 respectively). Patients who had phymatous rosacea are also more likely to be older males (OR: 3.82 95% CI 1.64–8.92, P = 0.002). Conclusion: The epidemiology and outcome of rosacea among local patients were studied. Rosacea is more common among certain racial groups such as Chinese, Caucasian, and other races. The clinical subtypes also seem to be related to races of certain skin colors and might be related to varied natural intrinsic responses to the sun among different racial groups.